(untitled) (Journal of Human Sciences, 2022)
The research sheds light on one of the qur’an’s guides in dealing with the danger of rumors on homelands. They are considered dangerous and threatening security and stability. The researcher tried to link between the qur’anic verses, and what happened of incidents to the prophet muhammad, may allah prayers and peace be upon him and his companions. This research also discusses how the holy qur’an addresses the danger of rumors, and determining the ways and the solutions that the prophet muhammad, may allah blesses him and grant him peace, embodied in facing these various rumors: social, political, economic, intellectual, and others.